Species distribution and in vitro antimicrobial susceptibility of coagulase-negative staphylococci isolated from bovine mastitic milk. Issue 1 (December 2015) - Taponen, Suvi; Nykäsenoja, Suvi; Pohjanvirta, Tarja; Pitkälä, Anna; Pyörälä, Satu
Abstract Background Coagulase-negative staphylococci (CoNS) are the most common bovine mastitis causing bacteria in many countries. It is known that resistance for antimicrobials is in general more common in CoNS than inStaphylococcus aureus but little is known about the antimicrobial resistance of specific CoNS species. In this study, 400 CoNS isolates from bovine mastitic milk samples were identified to species level using ribotyping and MALDI-TOF MS, and their antimicrobial susceptibility was determined using a commercially available microdilution system. The results were interpreted according to the epidemiological cut-off values by the European Committee on Antimicrobial Susceptibility testing. Results The most common CoNS species wereS. simulans, S. epidermidis, S. chromogenes andS. haemolyticus. Penicillin resistance was the most common type of antimicrobial resistance.Staphylococcus epidermidis was the most resistant among the four major species. Almost one-third of ourS. epidermidis isolates were resistant to >2 antimicrobials and close to 7 % were multidrug resistant. The majority ofS. epidermidis isolates were resistant to benzylpenicillin. On the contrary, only fewS. simulans isolates were penicillin-resistant. Phenotypic oxacillin resistance was found in all four main species, and 34 % of the isolates were oxacillin resistant. However, only 21 isolates (5 %) were positive for themec A gene. Of these, 20 wereS. epidermidis and oneS. sciuri .mec C positive isolates were not found. Conclusion Staphylococcus epidermidis differed from the three other major CoNS species as resistance to the tested antimicrobials was common, several isolates were multidrug resistant, and 19 % of the isolates carried themec A gene encoding methicillin resistance.